The Role of the Social Welfare Service in Community Empowerment in NA IX-X District, North Labuhanbatu Regency - Irawan, Muhammad Sahid; Mailin, Mailin (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
The policy of the Labura District Government plays a crucial role in overseeing and facilitating development in the region. The area can effectively and sustainably manage its development when complemented by a well-crafted RPJM (Regional Medium-Term Development Plan) and efficient organizational roles. The purpose of this study is to elaborate on the contribution of the Social Welfare Office to the empowerment of district communities. North Labuhanbatu Regency, NA IX-X. Obstacles to this program are usually found in remote locations, which may make it difficult for the Social Welfare Office to help those in need and strengthen communities in the NA IX-X District of North Labuhanbatu Regency. Qualitative data analysis methods such as literature review, interviews, and observations were used in this research approach. The study's findings suggest that, in line with community empowerment theory, they will help facilitate community participation to increase resource capacity. However, due to poor coordination, the role of the Social Welfare Office as a stakeholder in community empowerment for poverty alleviation, including planning, data collection, and assistance, is not optimal in fulfilling its obligations. Data collection of Family Hope Program recipients needs to be corrected on target in all local governments.